Implementasi Metode CPM, Crashing dan PERT Pada Penjadwalan Proyek Pembangunan Masjid dan Asrama Yatim Piatu Barokah Amanah Mustaqbal - Sutrisno Sutrisno; Audi Pramudya; Rudi Effendi Listyanto (Jurnal Serambi Engineering, 2023)
Scheduling is one of many project management activities that have a crucial role and support the success of a project. The existence of good scheduling is able to minimize delays in project completion and swelling of the budget costs incurred. This study aims to identify the optimal completion time, determine alternative acceleration, as well as the probability of completing the target duration for the construction project of Mosque and Orphan Dormitory Barokah Amanah Mustaqbal Foundation, Karawang. Based on analysis of CPM and PERT, critical path activities are A-C-D-E-F-G-H-K-M-N-O-P-Q-R-S-T with time completion faster than the target set for 90 days. In the CPM method, the project completion time takes 87 days. These results can also be accelerated by crashing programs on 7 alternative project activities, there is: M-P-O-EQ-H-S. Crashing for a maximum of 8 days requires an increase in labor costs of 6,09% (Rp10.954.109) of the initial cost. The PERT method shows that a project duration of 86,7 days at probability level that can be completed in less than 90 days of 91,31%.